ORGAN DALAM BABI BALI YANG DIBERI PAKAN KONSENTRAT PROTEIN LIMBAH PETERNAKAN AYAM (KPLA) - A. F. G. S. Pande; I N. T. Ariana; I. N. S. Sutama (Jurnal Peternakan Tropika, 2025)
Feeding chicken farm waste protein concentrate (KPLA) can increase the quality and edible offal weight of bali pigs . This research aims to determine the edible offal weight of bali pigs based on KPLA. The research was carried out for 2 months and 2 weeks in the pig pen at the Bukit Jimbaran Research Station/Farm, Faculty of Animal Husbandry, Udayana University, using a completely randomized design with 3 treatments and 5 replications. Treatment consisted of T0: 24% CP-152+0% KPLA; T1: 12% CP-152+12% KPLA; T2: 0% CP-152+24% KPLA. The variables observed were the percentage of percentage of liver weight, percentage of lung weight, percentage of small intestine weight, percentage of large intestine weight, percentage of stomach weight, and percentage of blood weight. The results showed that the percentage of liver weight and lung weight in T2 treatment tended to be higher at 1.224±0.031%; 1.928±0.097%. The percentage of small intestine weight tended to be higher in the control treatment 1.712±0.04%. The percentage of large intestine weight and stomach weight tended to be higher in the T2 treatment at 1.494±0.035% and 0.864±0.018%, while the percentage of blood weight was significantly highest (P<0.05) in the T2 treatment at 3.682±0.112%. It was concluded that KPLA replacement was able to maintain the edible offal weight of bali pigs. ABSTRAK Pemberian pakan konsentrat protein limbah peternakan ayam (KPLA) mampu menambah kualitas dan berat organ dalam babi bali. Penelitian ini bertujuan untuk mengetahui pemberian KPLA terhadap organ dalam babi bali. Penelitian dilaksanakan selama 2 bulan 2 minggu di kandang babi Stasiun Penelitian/Farm Bukit Jimbaran Fakultas Peternakan Universitas Udayana yang menggunakan rancangan acak lengkap dengan 3 perlakuan dan 5 ulangan. Perlakuan terdiri dari T0 : Ransum 24 % Konsentrat CP-152 + 0% KPLA (Kontrol); T1 : Ransum 12% Konsentrat CP-152 + 12% KPLA; T2 : Ransum 0% Konsentrat CP-152 + 24 % KPLA. Variabel yang diamati adalah persentase berat hati, persentase berat paru-paru, persentase berat usus halus, persentase berat usus besar, persentase berat lambung, dan persentase berat darah. Hasil penelitian menunjukkan persentase berat hati, berat paru-paru pada perlakuan T2 adalah cenderung lebih tinggi sebesar 1,224 ± 0,031%; 1,928 ± 0,097%. Persentase berat usus halus adalah cenderung lebih tinggi pada perlakuan kontrol (T0) sebesar 1,712 ± 0,04%. Persentase berat usus besar dan berat lambung adalah cenderung lebih tinggi pada perlakuan T2 sebesar 1,494 ± 0,035% dan 0,864 ± 0,018%, sedangkan persentase berat darah adalah nyata tertinggi (P<0,05) pada perlakuan T2 sebesar 3,682 ± 0,112%. Disimpukan bahwa penggantian KPLA mampu mempertahankan berat organ dalam babi bali